2018
DOI: 10.1007/978-3-030-01851-1_35
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Reasoning with Layered Preferences

Abstract: Temporal representation and temporal reasoning is a central in Artificial Intelligence. The literature is moving to the treatment of "non-crisp" temporal constraints, in which also preferences or probabilities are considered. However, most approaches only support numeric preferences, while, in many domain applications, users naturally operate on "layered" scales of values (e.g., Low, Medium, High), which are domain-and task-dependent. For many tasks, including decision support, the evaluation of the minimal ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Luckily, in BoDs both computing the minimal network of constraints of a problem and answering queries using it can be done in polynomial time and space (e.g., using algorithms like the Floyd-Warshall's one [28]). [4] generalizes and extends the 3 Notice that structures similar to the minimal network can be obtained also for other classes of CSPs. However, computing them often requires nonpolynomial space and/or time.…”
Section: Non-crisp Bods and Bods With Preferencesmentioning
confidence: 91%
See 4 more Smart Citations
“…Luckily, in BoDs both computing the minimal network of constraints of a problem and answering queries using it can be done in polynomial time and space (e.g., using algorithms like the Floyd-Warshall's one [28]). [4] generalizes and extends the 3 Notice that structures similar to the minimal network can be obtained also for other classes of CSPs. However, computing them often requires nonpolynomial space and/or time.…”
Section: Non-crisp Bods and Bods With Preferencesmentioning
confidence: 91%
“…They showed that, by exploiting c-semirings in the treatment of preferences, it is possible to achieve tractability. The approaches by Andolina et al [60], Anselma et al [4] and Khatib et al [37] are the closest ones to ours: a detailed comparison with such approaches is reported in Section 7 after the description of our approach.…”
Section: Non-crisp Bods and Bods With Preferencesmentioning
confidence: 96%
See 3 more Smart Citations